Numerical Analysis of Oxygen Adsorption on SnO2 Surface Using Slab Geometry - Weronika Izydorczyk (Advances in Condensed Matter Physics)
Oxidation of thin film SnO2 layer was simulated. In particular, the evolution of depletion layer was investigated by solving Poisson-Boltzmann equation for SnO2 slab geometry grains. On this basis, the surface energy barrier dependence on layer thickness (30–500 nm) was obtained. The effect of the donor mobility (oxygen vacancies in the bulk) and degree of donor ionization on electric potential inside layer with different thicknesses was discussed. Furthermore, the dependence of per-square conductance on temperature (from 400 K to 700 K) has been computed. It was assumed that the bulk oxygen vacancies (donors) are singly or doubly ionized and mobile. The temperature variations in the carrier mobility were also taken into account.